KAMPANYE PRA PEMILU 1955: ANTARA PARTAI PNI, MASYUMI, NAHDATUL ULAMA, DAN PKI HINGGA DAMPAK PASCA PEMILU 1955 - Pipit Nur'Aini (Keraton: Journal of History Education and Culture, 2024)
Democracy is seen as a political system and procedures for organizing life in society, especially in Indonesia. With democracy, this is closely related to the general election or election process. Since the proclamation of Indonesian independence, elections have been held eight times. The first elections took place in 1955 which resulted in a constituent body and the DPR. The 1955 election was participated by many parties and became one of the major events after Indonesian independence. In this article, the author wants to discuss the 1955 pre-election campaign that took place in Indonesia. The main problem raised by this author is the campaign and political battles leading up to the 1955 election as well as the impact after the 1955 election. In this context, the author uses historical writing methods, including collecting sources, verifying sources, interpreting and writing history. The results of the writing show that the campaigns and political battles carried out by the PNI, Masyumi, Nahdatul Ulama and PKI parties have their own ideologies, methods and methods for obtaining as many votes as possible. Unfortunately, after the 1955 election there was a lot of socio-political turmoil, including conflict between various components and elites, which then reached its peak in the Presidential Decree of July 5 1959, where President Soekarno replaced the era of liberal democracy with guided democracy.